Laser-induced ultrafast insulator-metal transition in BaBiO_{3} - Alexander E. Lukyanov; Vyacheslav D. Neverov; Yaroslav V. Zhumagulov; Alexey P. Menushenkov; Andrey V. Krasavin; Alexei Vagov (Physical Review Research, 2020)
We investigate ultrafast coherent quantum dynamics of undoped BaBiO_{3} driven by a strong laser pulse. Our calculations demonstrate that in a wide range of radiation frequencies and intensities the system undergoes a transient change from the insulating to the metallic state, where the charge density wave and the corresponding energy spectrum gap vanish. The transition takes place on the ultrafast timescale of tens femtoseconds, comparable to the period of the corresponding lattice vibrations. The dynamics are determined by a complex interplay of the particle-hole excitation over the gap and of the tunneling through it, giving rise to the highly nontrivial time evolution which comprises high harmonics and reveals periodic reappearance of the gap. The time evolution is obtained by solving the dynamical mean-field theory equations with the realistic parameters for the system and radiation. Results are summarized in the phase diagram, helpful for a possible experimental setup to achieve a dynamical control over the conduction state of this and other materials with the similarly strong electron-phonon interaction.